A catalyst-coated diaphragm assembly to improve the performance and energy efficiency of alkaline water electrolysers - Zhuang Xu; Yanying Liu; Xiaobo Cheng; Yunshan Shang; Yongtao Wang; Jing Wang; Wenshi Li; Guangli He (Communications Engineering)
Abstract Alkaline water electrolysers are ideal for gigawatt-scale hydrogen production due to the usage of non-precious metal and low-cost raw materials. However, their performances are modest with the separated electrode and diaphragm structure which can date back to more than 100 years ago. Here we report a catalyst-coated diaphragm assembly to improve the performance of alkaline water electrolysers. The transport resistance of OH- ions is reduced and the electrochemical surface area of catalysts is enlarged by more than forty fold, representing more than 40% increase in hydrogen production rate or as much as 16% reduction in energy consumption. The electrolyser with our catalyst-coated diaphragm assembly delivers current densities as high as 1 A cm−2 at 1.8 V or 2 A cm−2 at 2 V and shows good stability after more than 1000 hours of operation. Therefore, the catalyst-coated diaphragm assembly route is promising for the development of high-performance and efficient alkaline water electrolysers.